Reformulasi Fiqih Kontemporer dalam Perspektif Fazlur Rahman - Muhammad, Pauzi; Ridwan, Muannif (Studi Multidisipliner: Jurnal Kajian Keislaman, 2021)
Fiqih is a set of rules or laws for every Moslem mukallaf, explored and formulated and determined from detailed arguments. Fiqih has dynamic, elastic characteristics, and is suitable for every place and time until the end of time. So that fiqih can be reformulated or formulated and redefined appropriately in accordance with the times, due to changes and new problems that arise in the lives of Moslems. Among the modern reformist figures of Islam, Fazlur Rahman, offers this method of fiqih reformulation, with a number of methods of ijtihad. It provides new innovations in fiqih formulations, with a distinctive style. This study will add to the scientific treasures of fiqih experts, researchers, and contemporary Islamic intellectuals